Effect and mechanism of mGluR6 on the biological function of rat embryonic neural stem cells. Issue 6 (3rd June 2019) - Zhang, Jing; Zhang, Lu; Chen, Yani; Shi, Haiyan; Huang, Xiaoyong; Wang, Yanfeng; Wang, Yu; Wei, Yameng; Xue, Wanjuan; Han, Jiming
ABSTRACT: Here, we investigated the effects and molecular mechanisms of metabotropic glutamate receptor 6 (mGluR6) on rat embryonic neural stem cells (NSCs). Overexpression of mGluR6 significantly promoted the proliferation of NSCs and increased the diameter of neutrospheres after treatment for 24 h, 48 h and 72 h. Overexpression of mGluR6 promoted G1 to S phase transition, with significantly decreased cell ratio in G1/G0 phase but significantly increased cell ratio in S phase. Additionally, mGluR6 overexpression for 48 h decreased the early and late apoptosis significantly. Moreover, overexpression of mGluR6 significantly increased the expression of p-ERK1/2, Cyclin D1 and CDK2, while the expression of p-p38 was significantly decreased. On the contrary, these effects of mGluR6 overexpression were reversed by mGluR6 knockdown. In conclusion, mGluR6 promotes the proliferation of NSCs by activation of ERK1/2-Cyclin D1/CDK2 signaling pathway and inhibits the apoptosis of NSCs by blockage of the p38 MAPK signaling pathway. Graphical abstract: : mGluR6 promotes the proliferation of NSCs via ERK1/2-Cyclin D1/CDK2 pathway and inhibits apoptosis of NSCs by blockage of the p38 MAPK pathway.